Pengaturan Tindak Pidana dalam Qanun Aceh: Komparasi Antara Qanun No. 12, 13, 14 Tahun 2003 dengan Qanun No. 6 Tahun 2014 (Mazahib, 2017)
The authority of the implementation of Shariah given by the Government of Indonesia to the Government of Aceh is the Shari'a in a broad sense, namely the guidance of Islamic teachings in all aspects of life. Consequently, it then includes the implementation of Islamic criminal law in the form of qanun (laws established by Muslim sovereign) in Aceh.  Yet, its application was limited to certain aspects of offences in Islam, and its drafting as well as deliberation were hasty. They were Qanun No. 12 (Khamr / consumption of liquor), 13 (Maisir / gambling) and 14 (Khalwat / being alone with someone of the opposite sex who is not a spouse or a relative) which were adopted in 2003. the selection of these three qanun was not without reason. The first reason, these three types of offences are a form of immoral deeds in the Shari'a and are very disturbing community, but have not been handled properly. Secondly, the euphoria of the society in the form of extra-judicial sentences by the people against these three types of offences. To prevent vigilantism, the aforementioned three qanun were enacted as a form of anticipation of the various chaoses in the Aceh community. This study examines the weaknesses contained in the Qanun 12, 13 and 14 Year 2003 and how the new qanun no. 6 Year 2014 concerning Qanun Jinayat Aceh overcome them. This paper argues that the weaknesses that exist in the old qanun have been covered by new qanuns because of more attention to the theory of Islamic law, the principle of Islamic criminal law, and, even to some extent, the principles of human rights were given in its deliberation.Keywords: Qanun, Khamar, Maisir, Khalwat, Jināyāt.